The Role of Basic Athletic Skills in the Formation of Sports Technical Ability: A Systematic Review - Daulay, Dicky Edwar; Ardiansyah, Angga; Panjaitan, Ahmad Rifai; Padang, Elpindo Supahman; Octova, Adryo (PENJAGA : Pendidikan Jasmani dan Olahraga, 2026)
Basic athletic skills are the main foundation in the development of sports technical abilities, but studies that comprehensively explain the relationship between the two are still limited. This study aims to analyze the role of basic athletic skills in the formation of sports technical abilities through a systematic literature review approach. This study uses a literature review method with reference to the PRISMA principle. Data sources were obtained from scientific journal articles through Google Scholar and national journal portals with certain inclusion criteria. From the search results, 8 articles were obtained that met the criteria for analysis. The analysis was carried out through the stages of identification, selection, synthesis, and drawing conclusions. The results of the study indicate that basic athletic skills contribute to the formation of sports technical abilities by improving motor skills, movement coordination, and body control. Basic movements such as running, jumping, and throwing serve as a foundation for learning more complex sports techniques. These findings confirm that basic athletic skills have a strategic role as a conceptual basis in systematic sports learning and training